Financing pathways for entrepreneurs in the Philippines: A big data analysis using DSLOGIT regression - Cruz, Liezel S.; Rahnema, Leila (Philippine Management Review; Vol 32 No 1 (2025): Philippine Management Review, 2025)
As echoed by many other authors and experts, micro, small, and medium enterprises (MSMEs) are crucial for economic development. This study uses the 2014 Consumer Finance Survey conducted by the Bangko Sentral ng Pilipinas and a double-selection lasso logistic regression model (DSLOGIT) to identify factors influencing the likelihood of starting and operating single proprietorships in the Philippines. The findings highlight the significant role of various financing sources and individual characteristics. Microfinancing is positively correlated with single proprietorship, while loans from commercial banks, cooperatives, and close relatives negatively affect business ownership. These insights can help policymakers design more effective support mechanisms for MSMEs.